IMPLEMENTASI PERATURAN BUPATI NOMOR 61 TAHUN 2021 TENTANG ALOKASI DANA DESA DI DESA PULAU ARO KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2022 - Nupus, Gulam Syahdi; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Based on Regent Regulation Number 61 of 2021, Village Fund Allocation (ADD) is a balanced fund allocated from the Regency/City Regional Revenue and Expenditure Budget (APBD) to villages, after deducting the Special Allocation Fund to assist in financing government activities, development, and village community empowerment. The purpose of this study is to determine the implementation of Regent Regulation Number 61 of 2021 concerning the Village Fund Allocation in Pulau Aro Village, Kuantan Tengah District, Kuantan Singingi Regency, and to determine the factors involved in implementing the Village Fund Allocation policy in Pulau Aro Village, Kuantan Tengah District, Kuantan Singingi Regency in 2022. This research employed a qualitative approach with descriptive methods, conducted in Pulau Aro Village, Kuantan Tengah District, Kuantan Singingi Regency. Primary and secondary data were used, and data collection techniques included interviews and documentation. Informants were selected purposively, including the Village Head, the Head of the Village Consultative Body (BPD), the Village Secretary, relevant Village Officials, and Youth/Community Leaders. Data were analyzed using the Huberman and Miller model, with data validity checked through extended participation to strengthen trust and triangulation to verify data from various sources and tools. The results indicate that the implementation of Regent Regulation Number 61 of 2021 concerning Village Allocation Funds (ADD) in Pulau Aro Village is suboptimal because ADD is used for village budget allocations (Siltap) and village official allowances, whereas Perbub Number 61 of 2021 outlines more complex uses of ADD. Keywords: Implementation, Village Fund Allocation (ADD), Qualitative Descriptive